Globalized peripheries : Central Europe and the Atlantic world, 1680-1860 - Wimmler, Jutta; Weber, Klaus, 1960 February 18- (People, markets, goods ;, 2020)
The early modern Atlantic world, with its flows of bullion, of free and unfree labourers, of colonial produce and of manufactures from Europe and Asia, with mercantile networks and rent-seeking capital, has to date been described almost entirely as the preserve of the Western sea powers. More recent scholarship has rediscovered the dense entanglements with Central and Eastern Europe. Globalized Peripheries goes further by looking beyond slavery and American plantations. Contributions look at the trading practices and networks of merchants established in Central and Eastern Europe, investigate commodity flows between these regions and the Atlantic world, and explore the production of export commodities, two-way migration as well as financial ties. The volume uncovers new economic and financial connections between Prussia, the Habsburg Empire, Russia, as well as northern and western Germany with the Atlantic world. Its period coverage connects the end of the early modern world with the long eighteenth century.